Expanding the potential of antibody–drug conjugates in gastrointestinal malignancies: beyond HER2 targets - P. Ntellas; A. Athauda; K. Sugiyama; M.L. Le; V. Crespi; I. Chau (ESMO Gastrointestinal Oncology)
Antibody–drug conjugates (ADCs) are an emerging class of targeted cancer therapeutics, combining the specificity of monoclonal antibodies with the potency of cytotoxic agents to deliver localized treatment while minimizing off-target effects. Recent advancements in ADC design focus on optimizing payloads, improving linker stability, and selecting effective target antigens. Additionally, innovative approaches such as small-molecule drug conjugates, immune-stimulating payloads, and bispecific or biparatopic antibodies are being explored to enhance specificity and efficacy. Despite challenges like neutralizing antibodies, toxicity, and variable efficacy, several ADCs have shown promise in patients with solid tumours. Particularly, in gastrointestinal cancers, ADCs targeting antigens such as claudin 18.2, c-MET, and CEACAM5 have demonstrated clinical activity offering potential alternatives to traditional human epidermal growth factor receptor 2 (HER2)-based therapies. Ongoing efforts to refine ADCs and explore novel formats offer significant potential to transform the treatment landscape of gastrointestinal cancers. This review examines the current state of ADC development for gastrointestinal malignancies, focusing on emerging targets and strategies beyond HER2.